Situation analysis and recommendations for information dissemination strategies in integrated health post x empowerment efforts - Putri Fitria Listi; Hanum Haniefa; Ayu Ekayanti; Nasywa Aulia; Aura Nurani Pangastiti; Tathia Rizky Amalia; Agustin Putri Rahayu; Lies Permana; Mohammad Fikri; Nur Rohmah; Annisa Nurrachmawati; Alma Feriyanti (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: The Integrated Health Post plays an important role as a community-based health effort (UKBM) in improving basic health services. However, low community participation was found at Integrated Health Post X in Samarinda City. This was due to the ineffective dissemination of information, both online and offline, which was exacerbated by limited information media, low access to technology, and a lack of coordination between stakeholders. Purpose: To identify the root causes of low community participation and formulate empowerment strategies through improvements to the Integrated Health Post activity information dissemination system. Method: The research used qualitative ethnography through surveys, observations, in-depth interviews, Focus Group Discussions (FGD) with USG tools, and in-depth interviews with cadres, neighborhood units (RT), and the community. Problem analysis was conducted using a Fishbone Diagram and strategy formulation through a Plan of Action based on input, process, output, and outcome indicators. Result: The analysis showed that the main cause of low community participation was ineffective information dissemination. The solutions produced included the formation of an information team, training in digital content creation, utilization of social media, and direct delivery of information by utilizing existing potential. Conclusion: This study shows low community attendance at Integrated Health Post X due to suboptimal information dissemination. Limited media, technological access gaps, and the absence of an organized information system prevent residents from receiving information in a timely manner. Situation analysis, focus group discussions, and in-depth interviews identified information dissemination as the main problem. Improvements are focused on forming a special team and training content creation to maximize digital media and direct communication. This strategy is expected to increase information reach, coordination, and community participation.